THE MEDIATING EFFECT OF PROFITABILITY ON LIQUIDITY AND CAPITAL STRUCTURE ON COMPANY GROWTH: EMPIRICAL EVIDENCE FROM JAKARTA ISLAMIC INDEX (JII) COMPANIES - Arisnawati, Nur Fani; Utami, Yunita Lisnaningtyas (Universitas Muhammadiyah Tangerang, 2025)
The purpose of this study was to determine the mediating effect of profitability on liquidity and capital structure on company growth with empirical evidence from the Jakarta Islamic Index (JII). The research used is the quantitative method. The subjects used 17 companies listed JII for 2021-2023. The data analysis used is path analysis, hypothesis testing, the coefficient of determination, path calculation, and the Sobel test. The results of the study are that the liquidity variable (X1) on profitability has no effect and is not significant. The liquidity variable (X1) on profitability has no effect and is not significant. The liquidity variable has no effect on company growth and is not significant. Capital structure variable has no effect on company growth and is not significant. Profitability variable has a positive and significant effect on company growth. Profitability variable cannot affect the relationship between liquidity (X1) and profitability. Profitability variable cannot mediate the effect of capital structure variable on company growth.